Is there a skills crisis? Trends in job skill requirements, technology, and wage inequality in the United States - Michael J. Handel (Levy Economics Institute of Bard College, 2000)
Despite seven years of economic growth a large gap exists in the wages earned by workers at the top of the earnings scale and those at the bottom. The leading explanation for this growth in wage inequality continues to be the skills-mismatch theory. This theory in part posits that gains in technology have resulted in jobs having highly technical skill requirements that have outpaced growth in worker skills; demand for highly skilled workers therefore rises more swiftly than that for less-skilled workers, creating upward pressure on wages for those with the most skills. The empirical evidence is examined here and shows that there is little evidence to support the mismatch theory as there has been little sign of a shortage of workers with computer or general technical skills. If the analysis is correct, then policies currently used to close the wage gap, such as improved education and training, will not alone solve the inequality problem. Rather, the solution may require macroeconomic policies aimed at maintaining economic growth and full employment, and labor policies, such as the minimum wage, that support the earnings of workers at the lower end of the wage scale.
Keywords: 330; Lohnstruktur; Facharbeiter; Qualifikation; Berufsbildung; Erwerbspersonenpotenzial; USA